An epigenetic profile of early T‐cell development from multipotent progenitors to committed T‐cell descendants. Issue 4 (1st February 2014) - Vigano, Maria Alessandra; Ivanek, Robert; Balwierz, Piotr; Berninger, Philipp; van, Erik; Karjalainen, Klaus; Rolink, Antonius
<x xml:space="preserve">Abstract</x> Cellular differentiation of the T‐cell branch of the immune system begins with the HSC, which undergoes a series of stages characterized by progressive restriction in multipotency and acquisition of specific lineage identity At the molecular level, the restriction of cell potential, commitment, and differentiation to a specific lineage is achieved through the coordinated control of gene expression and epigenetic mechanisms. Here, we analyzed and compared the gene expression profiles and the genome‐wide histone modification marks H3K4me3 (H3 lysine 4 trimethylation) and H3K27me3 (H3 lysine 27 trimethylation) in (i) in vitro propagated HSCs, (ii) in vitro generated and propagated pro‐T cells derived from these stem cells, and (iii) double‐positive thymocytes derived from these pro‐T cells after injection into Rag‐deficient mice. The combined analyses of the different datasets in this unique experimental system highlighted the importance of both transcriptional and epigenetic repression in shaping the early phases of T‐cell development.